Dual-ligand PROTACS mediate superior target protein degradation in vitro and therapeutic efficacy in vivo - Chen, Yong; Xia, Zihan; Suwal, Ujjwal; Rappu, Pekka; Heino, Jyrki; De Wever, Olivier; De Geest, Bruno G. (ROYAL SOC CHEMISTRY, 2025)
Proteolysis targeting chimeras (PROTACs) are revolutionizing the drug development landscape due to their unique ability to selectively degrade disease-associated proteins. Conventional PROTACs are bivalent entities that induce ubiquitination and subsequent proteolysis of a chosen protein of interest (POI) by forming a ternary complex with an E3 ligase. We hypothesized that dual-ligand PROTACs, featuring two copies each of a POI ligand and an E3 ligase ligand, would facilitate the formation of high-avidity, long-lived ternary complexes inside cells, thereby increasing POI degradation potency. To this end, we developed a convergent synthesis route, using L-aspartic acid as a building block for homodimer synthesis, followed by copper-catalyzed azide-alkyne cycloaddition (CuAAC) to conjugate both dimers through a flexible linker. Dual-ligand PROTACs achieved up to a tenfold increase in degradation efficiency and a hundredfold increase in cytotoxicity in vitro across various cancer cell lines compared to their single-ligand counterparts. Furthermore, dual-ligand PROTACs sustain prolonged protein degradation, up to 60 hours after pulsing and washout. In vivo, in a mouse tumor model, the superior therapeutic activity of dual ligand PROTACs was observed.